PEMANFAATAN EDMODO UNTUK MEMPERSIAPKAN GURU MENGHADAPI PEMBELAJARAN ABAD 21 DI MGMP MATEMATIKA SMA KABUPATEN PONOROGO - Abadi Abadi; Dian Savitri; Budi Priyo Prawoto; Rudianto Artiono (Universitas Sanata Dharma, 2022)
In order to prepare students who are able to reason at a high level as well as skilled in using technology, it is necessary to hold a training activity for teachers to design and implement HOTS-oriented learning by utilizing Edmodo as a technology-based teaching medium. The training consisted of material reinforcement (the use of Edmodo, HOTS-oriented learning, preparation of HOTS questions) and workshops (teachers were guided in creating accounts and utilizing the features available in Edmodo as well as developing HOTS-oriented learning modules). The participants were able to inform more about the HOTS after training and about 18 teachers agreed that the participants had been able to construct their learning. In addition, there was also an increase in the ability of teachers to use Edmodo as a technology-based learning media. Of the 22 questionnaires submitted, 14 participants agreed that their understanding of Edmodo had increased and more than 90% of the training participants had been able to understand HOTS-based learning. In addition, although not many participants understand the use of Edmodo, the percentage was still above 50%. In general, 90% of the training participants believe that HOTS-based learning can be applied to the Edmodo as a learning medium.